Pengembangan Gerak Dasar Lari dan Lompat Melalui Pendekatan Bermain DiSekolah Dasar - - Yudanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
The movement skill development is the core of physical education programin elementary school. Teacher must take serious amount of attention to the developmentof the basic movement skill. This skill consists of locomotor basic move, non-locomotorand manipulation.The run and jump basic movement skills are included at the locomotors basicmovement skill. Through playing games, the development of these skills at elementaryschool can be achieved. Because kids always having their “moment of live” whenplaying games. Games also give benefit on several aspects such as physical,psychomotor, cognitive, and affective aspects.The development models can and must be adjusted along with the growth anddevelopment of the child, in order to achieve the result we wanted.Kata Kunci: Perkembangan, Gerak Dasar Lari dan Lompat, Bermain, Sekolah Dasar.